Implementation of Community Empowerment in the Health Posts of Islamic Boarding Schools - Chanif Kurnia Sari (GLOBAL HEALTH SCIENCE GROUP, 2022)
Poskestren is a place to seek health in a boarding school. The purpose of this study was to analyze the implementation of community empowerment in Islamic boarding schools in the poskestren environment. This study uses qualitative analysis methods, with 10 subjects. This research was carried out at the An-Nur Ngrungkem Islamic Boarding School Yogyakarta. The instruments used were camera, interview and observation guidelines. Data collection techniques used in-depth interviews, observation and documentation. The validity test used is source and technique triangulation and data analysis uses thematic analysis. Based on the results of research and discussion, it shows that there is an influence on leadership, potential, participation and knowledge of the Islamic boarding school community. The leadership has carried out the duties and functions of leadership such as controlling, monitoring, motivating, developing, public relations and decision makers. The potential and participation of the leader has been running as its function, while the potential of the students has already become husada students and as poskestren funders. Regarding the knowledge of the pesantren community, it needs to be improved, especially about PHBS. Poskestren will run well according to its function depending on the active role of the effectiveness of empowering the pesantren community.